Behavioural Analysis of Criminal Law: A Survey - Alon Harel (Bergen Journal of Criminal Law and Criminal Justice, 2014)
This article is a survey of behavioural analysis of criminal law. Behavioural analysis of criminal law exploits social science methodologies (behavioural economics, psychology and even sociology) to explore the effects of criminal law norms and enforcement policy on criminals, judges, juries, lawyers and other decision-makers, to determine the optimal type and size of criminal sanctions, to identify the optimal design of the enforcement system and the rules of evidence. Unlike traditional economic analysis, the behavioural perspective is eclectic rather than unitary; it is composed of various psychological and sociological findings including cognitive biases and their effects, prospect theory, the effects of social norms, findings concerning the ways preferences and beliefs are being shaped and even studies concerning happiness. Behavioural theorists call for the understanding and at times exploitation of various cognitive misperceptions, biases and heuristics to increase the deterrent effect of criminal law prohibitions and sanctions and/or increase their effectiveness. This survey compares this approach to traditional retributive approach and to economic analysis of law. It also provides several examples in which behavioural insights were used and, last it evaluates the prospects that the behavioural approach will influence policy and legislation.